THE CORRELATION BETWEEN READING MOTIVATION AND READING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 3 MENGWI IN ACADEMIC YEAR 2020/2021 - Ni Luh Eka Putri Haryani; Dewa Gede Agung Gana Kumara; Anak Agung Putri Maharani (Academic Journal on English Studies (AJOES), 2021)
This correlation study is aimed to find out the correlation between reading motivation andreading achievement of the eighth grade students of SMP Negeri 3 Mengwi in academic year2020/2021. The sample was chosen by cluster sampling as many as 64 students. Theinstrument used in this study was questionnaire and test; reading motivation questionnaireand reading achievement test. Reading motivation questionnaire is used to know the students’reading motivation while reading comprehension test is used to find out the students’ readingachievement in understanding a text. The obtained data were assessed by using ProductMoment’s formula and analyzed by using SPSS 23.0. Based on data analysis, it showed thatthere is high, significant and positive correlation between reading motivation and readingachievement of the eighth grade students of SMP Negeri 3 Mengwi in academic year2020/2021. Therefore, it answered the research question that there is a fair correlationbetween reading motivation and reading achievement.